Enzymes for pharmaceutical and therapeutic applications. (8th May 2020) - Meghwanshi, Gautam Kumar; Kaur, Navpreet; Verma, Swati; Dabi, Narendra Kumar; Vashishtha, Abhishek; Charan, P. D.; Purohit, Praveen; Bhandari, H.S.; Bhojak, N.; Kumar, Rajender
Abstract: Enzymes are highly efficient and selective biocatalysts, present in the living beings. They exist in enormous varieties in terms of the types of reactions catalyzed by them for instance oxidation–reduction, group transfers within the molecules or between the molecules, hydrolysis, isomerization, ligation, bond cleavage, and bond formation. Besides, enzyme based catalyses are performed with much higher fidelity, under mild reaction conditions and are highly efficient in terms of number of steps, giving them an edge over their chemical counter parts. The unique characteristics of enzymes makes them highly applicable fora number of chemical transformation reactions in pharmaceutical industries, such as group protection and deprotection, selective acylation and deacylation, selective hydrolysis, deracemization, kinetic resolution of racemic mixtures, esterification, transesterification, and many others. In this review, an overview of the enzymes, their production and their applications in pharmaceutical syntheses and enzyme therapies are presented with diagrams, reaction schemes and table for easy understanding of the readers. Abstract : Illustration of pharmaceutical enzymes production, recovery, processing, and application in different pharmaceutical synthesis/processing and therapeutics.